Quality of life, academic self-concept, and mental health in children with epilepsy: The possible role of epilepsy comorbidities - Brabcová, Dana Buršíková; Otáhalová, Adéla; Kohout, Jiří; Suleková, Michala; Mašková, Ivana; Bělohlávková, Anežka; Kršek, Pavel (Epilepsy & behavior, 2025)
PURPOSE: Epilepsy in children is often associated with impaired quality of life, lower academic achievement, and reduced academic self-concept, as well as an increased risk of depression and anxiety. This study aims to evaluate the possible impact of comorbidities, such as learning disabilities (LD) and attention deficit hyperactivity disorder (ADHD), on these variables. METHODS: A total of 104 children with epilepsy (CWE) aged 8-15 years, attending mainstream schools, participated in the study. Of these, 45 were diagnosed with LD and/or ADHD. Participants completed the CHEQOL-25 questionnaire to assess quality of life (QoL), the SPAS questionnaire to evaluate academic self-concept, as well as inventories measuring depressive and anxiety symptoms. The data were analyzed to identify differences between subgroups with and without LD/ADHD using a two-sample t-test. Additionally, correlation analysis was conducted to identify other relevant variables influencing QoL, academic self-concept, and depressive and anxiety symptoms. RESULTS: QoL and academic self-concept were significantly poorer in CWE with LD/ADHD compared to those without comorbidities. QoL showed statistically significant associations with depressive and anxiety symptoms, and academic self-concept. While depressive symptoms levels in CWE without comorbidities align with those in the general population, CWE with LD/ADHD showed an increased association with depressive symptoms. Although anxiety symptoms were relatively strongly associated with depressive symptoms, their prevalence remains broadly comparable to that of children without epilepsy, regardless of the presence of LD/ADHD. CONCLUSION: CWE with LD/ADHD and their families may benefit from focused attention, including targeted counseling and therapeutic interventions. However, specific interventional studies are recommended, based on child-specific findings.
Keywords: Anxiety; Comorbidity; dítě; Quality of life; Adolescent; Depression; poruchy učení; Academic self-concept; komorbidita; lidé; Attention Deficit Disorder with Hyperactivity; průzkumy a dotazníky; Mental Health; Female; deprese; Learning Disabilities; duševní zdraví; Epilepsy; Male; Surveys and Questionnaires; ženské pohlaví; kvalita života; Children with epilepsy; Child; Humans; mužské pohlaví; Quality of Life; sebepojetí; epilepsie; hyperkinetická porucha; úzkost; Learning disability; Self Concept; mladiství